Beta adrenergic blokade in myocardial infarction - Yusuf, S (1980)
﻿ This thesis is concerned with the influence of acute and long-term beta-adrenergic blockade on myocardial infarction in man. An original statistical evaluation of all published and some available unpublished clinical trials is presented in Chapter I. Chapter III and TV concern the measurement and evolution of infarct size in man. In Chapter III, praecordial ECG mapping and the standard 12 lead ECG have been correlated with cumulative release of the MB isomer of creatine kinase. Using these techniques, I have found that approximately 50% of eventual infarction is complete in 6 hours; implying that interventions designed to salvage ischaemic myocardium may be feasable (Chapter IV). In Chapter V, I have demonstrated delayed beta-adrenergic blockade after oral administration of atenolol and that an initial intravenous dose is essential to achieve early and effective beta-blockade. In a randomised control trial of 215 patients, atenolol administered intravenously within 12 hours of pain, prevented infarction in treated patients with initial threatened infarcts and reduced infarct size and morbidity in those with initial definite infarcts (Chapter VI). Patients with anterior myocardial infarction, randomised to receive atenolol for a year, showed significantly greater R wave recovery and Q wave disappearance on serial praecordial maps compared to placebo patients. In a further study, this was demonstrated to be due to lowering the heart rate. This phenomenon of improved EGG recovery with atenolol was reproduced in experimental infarction and was shown to be due to improved scar shrinkage (Chapter VII). The implications of these studies are discussed. It is likely that both early and long-term beta-blockade will be beneficial to patients with myocardial infarction.